2020
DOI: 10.3390/app10124335
|View full text |Cite
|
Sign up to set email alerts
|

Robust-Extended Kalman Filter and Long Short-Term Memory Combination to Enhance the Quality of Single Point Positioning

Abstract: In the recent years, multi-constellation and multi-frequency have improved the positioning precision in GNSS applications and significantly expanded the range of applications to new areas and services. However, the use of multiple signals presents advantages as well as disadvantages, since they may contain poor quality signals that negatively impact the position precision. The objective of this study is to improve the Single Point Positioning (SPP) accuracy using multi-GNSS data fusion. We propose the use of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In navigation and positioning, Tan et al used LSTM as a de-noising filter and proposed the rEKF-LSTM method to significantly improve single-point positioning accuracy [29]. Jiang et al proposed an LSTM-RNN algorithm to filter MEMS gyroscope outputs, and the results indicated that the method was effective for improving MEMS INS precision [30].…”
Section: Introductionmentioning
confidence: 99%
“…In navigation and positioning, Tan et al used LSTM as a de-noising filter and proposed the rEKF-LSTM method to significantly improve single-point positioning accuracy [29]. Jiang et al proposed an LSTM-RNN algorithm to filter MEMS gyroscope outputs, and the results indicated that the method was effective for improving MEMS INS precision [30].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, it is possible to use a combination of artificial neural networks (ANNs) with Kalman filters (KFs) [ 9 ] or even recurrent neural networks (RNNs) in order to estimate the new attitude [ 10 ]. These approaches require some previous attitude information in order to adjust the predictions, that is, they depend on time information.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many scholars have proposed a large number of corresponding improved filter algorithms for the nonlinearity and uncertainty of the actual navigation system as well as the non-gaussian and correlation of noise, etc. [26][27][28][29][30]. Reference [31] proposed an adaptive filter method based on the state observability.…”
Section: Introductionmentioning
confidence: 99%